PEMILIHAN MATERI PEMBELAJARAN APRESIASI PUISI BERKARAKTER BANGSA DALAM NILAI RELIGIUS - Prayitno Prayitno (Institut Agama Islam Negeri Purwokerto, 2014)
Teachers in pre-learning activities of appreciation of poetry in high school need to select appropriate learning materials in order to meet the curriculum 2013. In 2013, the educational curriculum is oriented to national values, because it is one of the parts of the character education, which consists of education of values, education of ethics, education of moral, and education of characters. One of the implementations of the character education is by selecting instructional materials for appreciation of poetry that focuses on religious and nation values. In the pre-stage of this learning activity, the teacher needs to prepare the content of the poem that contains character education, namely religious and nation values, by means of interpreting connotative words, ambiguity associated with denotative words, and interpreting the meaning of the poem to understand its meaning. An alternative learning material of appreciation of poetry in high school can be taken from W.S. Rendraâ€™s poems called Penance, After Confession, Come O God, Prayer of Hunger, and A Soldier's Prayer Before the War.Â Guru dalam tahap pra-kegiatan pembelajaran apresiasi puisi di Sekolah Menengah Atas perlu melaksanakan pemilihan materi pembelajaran yang sesuai dengan Kuriklum 2013. Dalam Kurikulum 2013 nilai pendidikan tersebut berorientasi kepada 18 nilai pendidikan karakter bangsa yang merupakan bagian dari pendidikan karakter yang terdiri atas pendidikan nilai, pendidikan budi pekerti, pendidikan moral, dan pendidikan watak. Salah satu implementasi nilai pendidikan berkarakter bangsa dalam pemilihan materi pembelajaran apresiasi puisi ini berfokus pada nilai religius. Pada tahap pra- kegiatan pembelajaran ini guru perlu mempersiapkan materi puisi yang mempunyai kandungan nilai-nilai pendidikan karakter bangsa, yaitu nilai religius dengan cara mengartikan kata-kata konotatif dan ambiguity yang dihubungkan dengan kata-kata denotatif, dan menginterpretasi makna dalambait puisi sehingga makna puisi secara keseluruhan dapat diketahui. Alternatif pemilihan materi pembelajaran apresiasi puisi di Sekolah Menengah Atas dapat diambil puisi-puisi karya W.S. Rendra yang berjudul Tobat, Setelah Pengakuan Dosa, Datanglah Ya Allah, Doa Orang Lapar, dan Doa Seorang Serdadu Sebelum Perang.